The importance of cleanrooms for the treatment of haemato-oncological patients - Holý, Ondřej; Matoušková, Ivanka (Contemporary Oncology/Współczesna Onkologia, 2012)
The main purpose of cleanrooms in health care centres is to prevent hospital infections or leakage of a highly infectious agent (the source of haemorrhagic fevers, SARS, etc.) into the ambient environment and subsequently possibly threatening other individuals. Patients with haematological malignancies or after autologous or allogeneic haematopoietic stem cell transplantation (HSCT) rank among immunosuppressed individuals. Prolonged and deep neutropenia is considered a key risk factor of the occurrence of an exogenous infection. One of the possibilities of preventing an exogenous infection in these patients is to place them in a “cleanroom” for the crucial period of time. Cleanrooms are intensive care units with reverse isolation. The final part of the general article below provides an overview of the technology and types of cleanrooms for immunosuppressed patients in compliance with the current recommendations and technical standards.